Between Cosmopolitan Ideals and State Sovereignty
X, 279 p.
Keywords: Between Cosmopolitan Ideals and State Sovereignty explores how philosophers and political theorists have recast principles of justice and human rights in the light of challenges posed by globalization. It discusses ethical issues that arise at a global level and considers whether human rights and sovereignty can ever be reconciled.